Credit Participation and Credit Source Selection of Vietnam Small and Medium Enterprise - Hoang, Nguyen Anh; Otake, Toshitsugu (UI Scholars Hub, 2014)
This study is an attempt to investigate the motivation behind the decision to participate in the credit market of SMEs from perspectives of behavioral finance and social capital theories. In addition, the study also examines the effect of behavioral finance and social capital factors on the credit source selection among SMEs. This study’s design strategy involves conducting questionnaire surveys to SMEs owners and statistical techniques to analyze the determinants of credit participation and credit source selection of borrowers. The findings showed that personal traits of SMEs owners/managers in terms of behavioral finance factors such as debt and risk attitudes, present biased and overconfidence and firms networking also have impacts on the firms’ credit participation and credit source selection. The research is one of the few studies that consider the influence of behavioral finance factors on firms financing decision. Furthermore, our result also contributes to explain the common use of informal credit market in developing countries.